2002
DOI: 10.1021/jp021545d
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared and Quasi-Elastic Neutron Scattering Investigations on the Binding States and the Dynamics of Benzene Molecules in the Pores of MCM-41 Molecular Sieves

Abstract: The in-plane C−H/C−C, out-of-plane C−H, and the fundamental ν19 C−C stretch vibrations of benzene molecules were monitored by FTIR spectroscopy, for adsorption in MCM-41 at room temperature and at different loadings. The results were compared with the corresponding data on ZSM-5 zeolites. The frequency and the relative intensity of IR bands point to the development of a compressed state of benzene in the pores of MCM-41, the density of which depended upon loading and lay in general between that of bulk liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Figure (b‐1) shows differential IR spectra obtained after introduction of gaseous benzene over TiO 2 / m ‐SiO 2 , H + ‐TiO 2 / m ‐SiO 2 and Cs + ‐TiO 2 / m ‐SiO 2 samples measured at room temperature. The bands observed at 1480 and 1471 cm −1 are assignable to the stretching vibration of benzene ring physisorbed and chemisorbed on samples, respectively . Over the series of M + ‐TiO 2 / m ‐SiO 2 samples, the intensity of the latter IR band decreased in the order of H + > Li + > Na + > K + > Rb + > Cs + (Figure (b‐2)), which well corresponds to the desorption temperature of chemisorbed benzene molecules determined from TG analysis.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Figure (b‐1) shows differential IR spectra obtained after introduction of gaseous benzene over TiO 2 / m ‐SiO 2 , H + ‐TiO 2 / m ‐SiO 2 and Cs + ‐TiO 2 / m ‐SiO 2 samples measured at room temperature. The bands observed at 1480 and 1471 cm −1 are assignable to the stretching vibration of benzene ring physisorbed and chemisorbed on samples, respectively . Over the series of M + ‐TiO 2 / m ‐SiO 2 samples, the intensity of the latter IR band decreased in the order of H + > Li + > Na + > K + > Rb + > Cs + (Figure (b‐2)), which well corresponds to the desorption temperature of chemisorbed benzene molecules determined from TG analysis.…”
Section: Resultssupporting
confidence: 66%
“…The bands observed at 1480 and 1471 cm À1 are assignable to the stretching vibration of benzene ring physisorbed and chemisorbed on samples, respectively. [38][39] Over the series of M + -TiO 2 /m-SiO 2 samples, the intensity of the latter IR band decreased in the order of H + > Li + > Na + > K + > Rb + > Cs + (Figure 4 (b-2)), which well corresponds to the desorption temperature of chemisorbed benzene molecules determined from TG analysis. This result again confirms that the interaction between benzene molecule and the solid surface decreases as the size of alkali metal cation increases.…”
Section: Investigation On Cation-p Interactionmentioning
confidence: 60%
“…Due to steric reasons, solvation is not probable with benzene molecules. There are several investigations pointing out that, at high coverage, benzene forms ordered structures in H-ZSM-5 [43,44,58]. We thus speculate that the band at 3175 cm À1 is due to interaction of bridging hydroxyls with benzene oligomers where the joint effect of two or more benzene molecules leads to an enhanced shift of the OH modes.…”
Section: Changes In the Oh/od Regions At High Benzene Coveragesmentioning
confidence: 65%
“…The dynamics of benzene in MCM-41 type materials has been investigated previously through both QENS and MD simulations; however, these investigations were limited to MCM-41 and not the catalyst Pt/MCM-41. The value of the diffusion coefficient of bulk liquid benzene has been thoroughly investigated through both experimental [5][6][7][8] and theoretical methods 9,10 and found to have a value of around 2.2 Â 10 À9 m 2 s À1 under ambient conditions. Earlier QENS studies 7,8 of benzene in MCM-41 found no difference between the bulk liquid diffusion coefficient and that of confined benzene.…”
Section: Introductionmentioning
confidence: 99%